Optimal culture conditions for neurosphere formation and neuronal differentiation from human dental pulp stem cells (Journal of Applied Oral Science, 2021)
Objectives: Human dental pulp stem cells (DPSCs) have been used to regenerate damaged nervous tissues. However, the methods of committing DPSCs into neural stem/progenitor cells (NSPCs) or neurospheres are highly diverse, resulting in many neuronal differentiation outcomes. This study aims to validate an optimal protocol for inducing DPSCs into neurospheres and neurons. Methodology: After isolation and characterization of mesenchymal stem cell identity, DPSCs were cultured in a NSPC induction medium and culture vessels. The durations of the culture, dissociation methods, and passage numbers of DPSCs were varied. Results: Neurosphere formation requires a special surface that inhibits cell attachment. Five-days was the most appropriate duration for generating proliferative neurospheres and they strongly expressed Nestin, an NSPC marker. Neurosphere reformation after being dissociated by the Accutase enzyme was significantly higher than other methods. Passage number of DPSCs did not affect neurosphere formation, but did influence neuronal differentiation. We found that the cells expressing a neuronal marker, β-tubulin III, and exhibiting neuronal morphology were significantly higher in the early passage of the DPSCs. Conclusion: These results suggest a guideline to obtain a high efficiency of neurospheres and neuronal differentiation from DPSCs for further study and neurodegeneration therapeutics.